KARAKTERISTIK FISIK KOMPOS TABLET SLOW RELEASE BERBAHAN DASAR BIOSLURY KOTORAN SAPI - Erni Romansyah; Karyanik Karyanik; Muhammad Fitrah; Mohammad Saharudin (Jurnal Agrotek Ummat, 2020)
The development Slow Release Compost Tablet can be used as a solution for the management of cow dung bioslurry by farmers. Bioslurry is a reject product from processing waste into biogas. The purpose of this study was to determine the physical characteristics of tablet compost made from cow dung Bio-slurry. The research design used a completely randomized design (CRD) with two factors, namely the composition of the addition of hydrogel  and silica from geothermal waste from the eruption of Mount Rinjani with five levels of treatment, namely; T1 (30gr hydrogel : 50gr silica powder); T2 (60gr hydrogel : 40gr silica powder); T3 (90gr hydrogel : 30gr silica powder); T4 (120gr hydrogel : 20gr silica powder); T5 (150gr hydrogel : 10gr silica powder). The results showed that the dimensions, weight, and hardness of tablet compost were not significantly different. The treatment without the addition of hydrogel  has the highest hardness value. The higher the hydrogel  addition, the lower the tablet compost hardness value.